HUMAN RESOURCE MANAGEMENT IN IMPROVING TEACHER PERFORMANCE AT MTS AL MUASYARAH BOGOR - Ahmad Idhofi; Febrianti (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2026)
Human resource management (HRM) plays a crucial role in creating an effective and productive learning environment. The proper implementation of HRM strategies can optimize teachers’ potential in terms of pedagogy, professionalism, as well as social and personal skills. This study aims to analyze the implementation of HRM at MTs Al-Muasyarah, which still faces several challenges, such as a limited number of teachers, suboptimal use of learning media, and discipline issues among some teachers. Employing a qualitative approach with a case study method through interviews, observations, and documentation, the findings reveal that HRM is carried out through workforce needs analysis, recruitment, training, performance evaluation, career planning, and payroll systems. Evaluations are conducted regularly through classroom supervision and administrative reviews, while teacher training is held 2–3 times a year to improve competencies. The implementation of these strategies has positively impacted teachers’ performance, as reflected in improved discipline, integrity, lesson planning skills, and the utilization of technology. In addition, teachers actively participate in seminars and training programs to broaden their professional insights. Thus, HRM at MTs Al-Muasyarah has proven to play a significant role in enhancing teachers’ performance both in pedagogical and professional aspects